MEKANISME DALAM PELAKSANAAN AKSESIBILITAS PENYANDANG DISABILITAS - RINDA PHILONA; NOVITA LISTYANINGRUM; DEWI ASMAWARDHANI; BAIQ NURAINI DWI S.; BAIHAQI SYAKBANI (Universitas Mahasaraswati K. Mataram, 2023)
In Law Article 41 Paragraph (2) Law no. 9 of 1999 concerning Human Rights it is written that: